Photosynthesis, pigments and ultrastructure of the alpine snow alga Chlamydomonas nivalis - Remias, Daniel; Lütz-Meindl, Ursula; Lütz, Cornelius (European journal of phycology, 2005)
Snow algae inhabit most of the cold regions worldwide, where long-lasting snow fields are common. The ecophysiology of snow algae has been studied intensively in North America and occasionally in polar regions. In the European Alps, the systematics of snow algae have been studied mainly by light microscopy. We studied temperature and light-dependence of photosynthesis, and plastid and extraplastid red pigment composition of red snow algae (Chlamydomonas nivalis) from snow patches in the high Alps of Austria. Both photosynthetic and respiratory data support the cryophilic adaptation of snow algal cells, but C. nivalis produced oxygen without any inhibition at temperatures up to 20°C and maintained this for 1 h, at irradiances up to 1800 µmol m −2 s −1 . Chlorophyll and primary carotenoid pigment composition was similar to that found in most other Chlorophyta. Additionally, large amounts of free and esterified astaxanthin were located in cytoplasmic lipid globules. Light and electron microscopy showed that the cell walls were frequently covered with tightly bound inorganic particles. Occasionally fungus- or bacteria-like structures were attached to the wall. The typical adult cell contained a single central chloroplast. Cytoplasmic structures were often difficult to resolve optically, as densely packed peripheral lipid globules, containing secondary carotenoids, occupied most of the cell volume. These pigments may shield the chloroplast from high irradiation (thus reducing the risk of photoinhibition) and may also be a potential carbon source during unfavourable climate conditions or the formation of daughter cells.